2004
DOI: 10.1007/s00127-004-0713-0
|View full text |Cite
|
Sign up to set email alerts
|

Substance misuse at presentation to an early psychosis program

Abstract: This study confirms the high rates of substance misuse, in particular cannabis, in first-episode psychosis. Implications for treatment are addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
106
3
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(127 citation statements)
references
References 0 publications
17
106
3
1
Order By: Relevance
“…The data are consistent with the literature, even if the prevalence of substance use we found is higher because we included any kind of use and not only categorically defined substance use disorders (Addington and Addington , 2007;Myles et al, 2012;Van Mastrigt et al, 2004). As in many previous studies (Coldham et al, 2002;Levy et al, 2012;Miller et al, 2011;Novak-Grubic and Tavcar, 2002;Verdoux et al, 2000), more than 40% of patients recruited showed poor adherence to their pharmacological treatment during the one year follow-up, but contrary to the published literature, this was not predicted by socio-demographic characteristics (Cotton et al, 2009;Perkins et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…The data are consistent with the literature, even if the prevalence of substance use we found is higher because we included any kind of use and not only categorically defined substance use disorders (Addington and Addington , 2007;Myles et al, 2012;Van Mastrigt et al, 2004). As in many previous studies (Coldham et al, 2002;Levy et al, 2012;Miller et al, 2011;Novak-Grubic and Tavcar, 2002;Verdoux et al, 2000), more than 40% of patients recruited showed poor adherence to their pharmacological treatment during the one year follow-up, but contrary to the published literature, this was not predicted by socio-demographic characteristics (Cotton et al, 2009;Perkins et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…The one-third incidence of positive samples for amphetamine among the studied Saudi patients raises the proposed question whether urine screening for possible drug abuse is necessary or not in patients with first episode psychosis. Our findings in addition to previous reports of the presence of substance misuse in the majority of people with first-episode psychosis that may have therapeutic implication [19,49,50] may support urine screening for possible drug abuse among psychotics. On the contrary, other investigators have not found any effect of routine urine drug screening in a psychiatric emergency service on disposition or the subsequent length of inpatient stays.…”
Section: Discussionsupporting
confidence: 82%
“…Literature data showed a prevalence of substance use in people with first episode psychosis of approximately double that in the general population of similar age [10,19,20]. Also, individuals with first episode psychosis may have a trend of increased sensitivity (supersensitivity hypothesis) to develop substance use disorder [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…This result is comparable with many studies which showed alcohol and cannabis to be most commonly used substance. 5,9 A study done in UK 8 , Germany 10 , Canada 11 , Australia 12 all showed high prevalence rate for both cannabis and alcohol use. However in all these studies cannabis was most commonly used substance followed by alcohol.…”
Section: Discussionmentioning
confidence: 99%